2017
DOI: 10.1111/bph.14078
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 activates PI3K/Akt signalling to protect human retinal pigment epithelial cells from amiodarone‐induced oxidative injury

Abstract: Amiodarone is one of the most effective anti-arrhythmic drugs available, but its clinical applications are limited by toxic side effects including optic toxicity. The purpose of this study was to investigate the toxic effect of amiodarone on D407 cells (a human retinal pigmented epithelial (RPE) cell line) and the mechanisms of the protective effect of insulin-like growth factor-1 (IGF-1). EXPERIMENTAL APPROACHThe involvement of the kinases, Akt and ERK, was analysed by Western blot. Intracellular accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Interestingly, this study showed that glucose temporally attenuated the induction of angiogenic IGF-1 of RPE cells, which was reversed by treating chrysin. A recent study shows that IGF-1 protects RPE cells from amiodarone-mediated injury via activation of PI3K/Akt signaling [ 40 ]. In this study, IGF-1 had potential as a protective agent for deterring the AGE-mediated toxicity of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study showed that glucose temporally attenuated the induction of angiogenic IGF-1 of RPE cells, which was reversed by treating chrysin. A recent study shows that IGF-1 protects RPE cells from amiodarone-mediated injury via activation of PI3K/Akt signaling [ 40 ]. In this study, IGF-1 had potential as a protective agent for deterring the AGE-mediated toxicity of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that Met significantly influences insulin‐like growth factor‐I (IGF‐I) gene expression (Wang et al, ). IGF‐I binds with its receptor in the cell membrane to activate the PI3K/Akt pathway (Liao et al, ), which plays a vital role in regulating glucose metabolism and maintaining glucose homeostasis (Bruce & Hanson, ; Hamann et al, ). The phosphorylation of Akt can induce the translocation of glucose from the cytoplasm to the plasma membrane through glucose transporter 4 (Patki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of serum and growth factors, Akt was phosphorylated and in turn phosphorylates FoxO3a, then FoxO3a was transported from the nucleus to the cytoplasm, where FoxO3a down‐regulates the expression of pro‐apoptosis molecules, such as Bax and Bcl‐2 . On the contrary, oxidative stress can induce FoxO3a from the cytoplasm to the nucleus, activate the target genes of FoxO3a, such as the pro‐apoptotic gene Bim, and induce cell apoptosis . The role of FoxO3a in oxidative stress‐induced cardiotoxicity has received attention.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 On the contrary, oxidative stress can induce FoxO3a from the cytoplasm to the nucleus, activate the target genes of FoxO3a, such as the pro-apoptotic gene Bim, and induce cell apoptosis. 37,38 The role of Figure 6). SNP induced FoxO3a translocation into the nucleus, increased the expression and activation of cleaved caspase-3, and inhibited the expression of Bcl-2, but had no effect on the expression of Bax (Figure 7).…”
Section: Discussionmentioning
confidence: 99%